Lipoprotein receptor loss in forebrain radial glia results in neurological deficits and severe seizures. Issue 12 (24th June 2020) - Bres, Ewa E.; Safina, Dina; Müller, Julia; Bedner, Peter; Yang, Honghong; Helluy, Xavier; Shchyglo, Olena; Jansen, Stephan; Mark, Melanie D.; Esser, Alexander; Steinhäuser, Christian; Herlitze, Stefan; et al.
Abstract: The Alzheimer disease‐associated multifunctional low‐density lipoprotein receptor‐related protein‐1 is expressed in the brain. Recent studies uncovered a role of this receptor for the appropriate functioning of neural stem cells, oligodendrocytes, and neurons. The constitutive knock‐out (KO) of the receptor is embryonically lethal. To unravel the receptors' role in the developing brain we generated a mouse mutant by specifically targeting radial glia stem cells of the dorsal telencephalon. The low‐density lipoprotein receptor‐related protein‐1 lineage‐restricted KO female and male mice, in contrast to available models, developed a severe neurological phenotype with generalized seizures during early postnatal development. The mechanism leading to a buildup of hyperexcitability and emergence of seizures was traced to a failure in adequate astrocyte development and deteriorated postsynaptic density integrity. The detected impairments in the astrocytic lineage: precocious maturation, reactive gliosis, abolished tissue plasminogen activator uptake, and loss of functionality emphasize the importance of this glial cell type for synaptic signaling in the developing brain. Together, the obtained results highlight the relevance of astrocytic low‐density lipoprotein receptor‐related protein‐1 for glutamatergic signaling in the context of neuron–glia interactions and stage this receptor as a contributing factor for epilepsy. Main Points: Lrp1 deletion in radial glia and their progeny leads to seizures, ventricular enlargement, ataxia. Lrp1 deletion impacts postnatal astrocyte development. Lrp1 loss in astrocytes impairs astrocytic tissue plasminogen activator uptake.